1994
DOI: 10.1161/01.str.25.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Relation of carotid artery wall thickness to diabetes mellitus, fasting glucose and insulin, body size, and physical activity. Atherosclerosis Risk in Communities (ARIC) Study Investigators.

Abstract: for the Atherosclerosis Risk in Communities (ARIC) Study InvestigatorsBackground and Purpose We tested the hypothesis that body mass, waist-to-hip circumference ratio, physical inactivity, diabetes, hyperglycemia, and fasting insulin are each positively associated with asymptomatic carotid artery wall thickness.Methods Average intimal-medial carotid wall thickness (an indicator of atherosclerosis) was measured noninvasively by B-mode ultrasonography in cross-sectional samples of 45-to 64 -year-old adults, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
192
5
17

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(231 citation statements)
references
References 40 publications
17
192
5
17
Order By: Relevance
“…10 Furthermore, the present study demonstrated that the sum of carotid IMT >1.1 mm and interadventitial diameter >8.0 mm is a significant independent predictor of multiple complex coronary lesions. Although abnormal glucose metabolism is positively associated with carotid intimal -medial wall thickness, 8 there were no differences in the mean, minimal, and maximal IMT between patients with and without DM in the present study. Therefore, our results suggest that carotid remodeling defined by absolute values may be appropriate for evaluation of systemic vascular remodeling.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…10 Furthermore, the present study demonstrated that the sum of carotid IMT >1.1 mm and interadventitial diameter >8.0 mm is a significant independent predictor of multiple complex coronary lesions. Although abnormal glucose metabolism is positively associated with carotid intimal -medial wall thickness, 8 there were no differences in the mean, minimal, and maximal IMT between patients with and without DM in the present study. Therefore, our results suggest that carotid remodeling defined by absolute values may be appropriate for evaluation of systemic vascular remodeling.…”
Section: Discussioncontrasting
confidence: 82%
“…The carotid intima -media thickness (IMT) has been proposed as a clinically useful marker for the development of atherosclerosis and may also serve as a marker of the response to therapy for atherosclerosis, as a predictor of acute cardiovascular events, and as a marker of advanced cardiovascular disease. 8,9 Our previous study demonstrated that patients with acute coronary syndrome (ACS) with multiple complex coronary plaques have a significantly larger carotid IMT and interadventitial diameter, and increased prevalence of carotid plaques than patients with solitary plaques. 10 The association between multiple complex coronary plaques and carotid artery remodeling suggests that plaque vulnerability may be a systemic phenomenon.…”
mentioning
confidence: 99%
“…15 Other surrogate methods, including fasting insulin, 16 Bennetts index 17 and the insulin-to-glucose ratio, 18 also demonstrate good concordance with values obtained using the more invasive techniques. [19][20][21] The recently developed quantitative insulin-sensitivity check index (QUICKI), 22 which takes the product of both the reciprocal and the logarithm of fasted insulin and glucose concentrations, gives values that correlate well with the glucose-clamp and minimal model techniques and may provide a better surrogate measure of insulin resistance compared to HOMA IR.…”
Section: Introductionmentioning
confidence: 75%
“…11,12 any vascular bed (Table 1). 6,9,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Progression of carotid atherosclerosis also is influenced by concomitant risk factors (Table 2). [31][32][33][34][35][36][37] Carotid atherosclerosis is commonly found in association with coronary and peripheral atherosclerosis.…”
Section: Methodsmentioning
confidence: 99%